Proteasome activity is required for the initiation of precancerous pancreatic lesions - Furuyama, Takaki (Sci Rep, 2016)
Proteasome activity is significantly increased in advanced cancers, but its role in cancer initiation is not clear, due to difficulties in monitoring this process in vivo. We established a line of transgenic mice that carried the ZsGreen-degron(ODC) (Gdeg) proteasome reporter to monitor the proteasome activity. In combination with Pdx-1-Cre;LSL-Kras(G12D) model, proteasome activity was investigated in the initiation of precancerous pancreatic lesions (PanINs). Normal pancreatic acini in Gdeg mice had low proteasome activity. By contrast, proteasome activity was increased in the PanIN lesions that developed in Gdeg;Pdx-1-Cre;LSL-Kras(G12D) mice. Caerulein administration to Gdeg;Pdx-1-Cre;LSL-Kras(G12D) mice induced constitutive elevation of proteasome activity in pancreatic tissues and accelerated PanIN formation. The proteasome inhibitor markedly reduced PanIN formation in Gdeg;Pdx-1-Cre;LSL-Kras(G12D) mice (P = 0.001), whereas it had no effect on PanIN lesions that had already formed. These observations indicated the significance of proteasome activity in the initiation of PanIN but not the maintenance per se. In addition, the expressions of pERK and its downstream factors including cyclin D1, NF-κB, and Cox2 were decreased after proteasome inhibition in PanINs. Our studies showed activation of proteasome is required specifically for the initiation of PanIN. The roles of proteasome in the early stages of pancreatic carcinogenesis warrant further investigation.